The Distribution of Inheritance in the Customary Law Community Before the Death of the Muwaris Reviewed from Islamic Law - Nawardi, Hamdan; Latupono, Barzah; Angga, La Ode (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The process of inheritance is to act as an alternative to the attitude of property ownership between the deceased and the person who leaves it, while according to the term it is something without which there will be no law, for example thaharah (purification) is a valid condition for prayer, if it is not cleaned before prayer, the prayer is undoubtedly invalid, however, doing thaharah, does not mean when you want to pray.Purposes of the Research: To find out and explain the factors behind the inheritance distribution system before the deceased in Gunung Village, South Buton Regency and to know and explain the views of Islamic law regarding inheritance distributed before the deceased died.Methods of the Research: The research method used in this writing is normative legal research. As for answering the problems in this study, the author uses three problem approaches, namely the statute approach, the case approach, and the conceptual approach. The procedure for collecting legal materials carried out by the author is to search and collect laws and regulations related to the legal issues faced. Laws and regulations in this case include both legislation and regulations. The analysis of legal materials uses a qualitative method, which is a study related to legal norms contained in international laws and regulations and legal norms in society.Findings of the Research: The results of this study show that the Distribution of Inheritance According to Islamic Law, which refers to Article 171 of the Compilation of Islamic Law, there are several provisions that have been stipulated in regulating inheritance. The view of Islamic law regarding inheritance distributed before the heir dies is that in Islamic law there is no division of inheritance before the heir dies, if this happens then in Islamic law it is called Hibah.